A novel fumarate hydratase-deficient HLRCC kidney cancer cell line, UOK268: a model of the Warburg effect in cancer - Yang, Youfeng (2012)
The role of energy deregulation and altered/adapted metabolism in tumor cells is an increasing important issue in understanding cancer. Hereditary leiomyomatosis renal cell carcinoma (HLRCC) is an aggressive form of RCC characterized by germline mutation of fumarate hydratase (FH) followed by somatic loss of the remaining wild type allele, and known to be a highly metastatic and lethal malignancy compared to other RCCs. The intrinsic loss of normal tricarboxylic acid (TCA) cycle presumably aids tumorigenesis due to the necessary metabolic alterations required and the enforced dependence on glycolysis derived energy, mimicking the Warburg effect. Thus, there is considerable utility in establishing a preclinical cell model from these tumors to study energy metabolism deregulation, as well as, developing new targeted therapeutic approaches for TCA cycle enzyme-deficient cancers. Here we describe a new immortalized cell line, UOK268, derived from a patient’s primary HLRCC-associated kidney cancer. This represents the first primary renal cell line to model TCA cycle gene loss and provides a perfect partner cell line to our previously described metastasis derived HLRCC-associated cell line, UOK262. We identified a novel germline FH missense mutation, p.His192Asp, and the subsequent loss of heterozygosity in UOK268. The UOK268 cell line expressed mutant FH protein, which localized to the mitochondria, but with loss of almost all catalytic activity. The UOK268 cells had severely compromised oxidative phosphorylation and increased glycolytic flux. Ingenuity® pathways analysis of hMitChip3 gene chip data confirmed the altered mRNA expression patterns of genes involved in several important pathways, such as lipid metabolism, apoptosis and energy production/glycolysis. UOK268 provides a unique model of a primary cell line demonstrating an enforced, irreversible Warburg effect and, combined with UOK262, provides a unique in vitro preclinical model for studying the bioenergetics of the Warburg effect in human cancer.